Integrated Ring‐Chain Design of a New Fluorinated Ether Solvent for High‐Voltage Lithium‐Metal Batteries. (10th March 2022) - Zhou, Tianhong; Zhao, Yan; El Kazzi, Mario; Choi, Jang Wook; Coskun, Ali
Abstract: Ether‐based electrolytes offer promising features such as high lithium‐ion solvation power and stable interface, yet their limited oxidation stability impedes application in high‐voltage Li‐metal batteries (LMBs). Whereas the fluorination of the ether backbone improves the oxidative stability, the resulting solvents lose their Li + ‐solvation ability. Therefore, the rational molecular design of solvents is essential to combine high redox stability with good ionic conductivity. Here, we report the synthesis of a new high‐voltage fluorinated ether solvent through integrated ring‐chain molecular design, which can be used as a single solvent while retaining high‐voltage stability. The controlled Li + ‐solvation environment even at low‐salt‐concentration (1 M or 2 M) enables a uniform and compact Li anode and an outstanding cycling stability in the Li|NCM811 full cell (20 μm Li foil, N/P ratio of 4). These results show the impact of molecular design of electrolytes towards the utilization of LMBs. Abstract : An integrated fluorinated ring‐chain molecular approach was developed through structural modification of a low‐cost, commercial ether for a new solvent 2‐ethoxy‐4‐(trifluoromethyl)‐1, 3‐dioxolane (cFTOF), which served as a single ether solvent for lithium‐metal batteries combining high‐voltage stability up to 6 V, and regulated Li + solvation structure, increasing Li + ion‐pairing with FSI anions in a low‐salt‐concentration electrolyte system.